Fall Risk in Adult Family Practice Non-Attenders: A Cross-Sectional Study from Slovenia - RUŽIĆ-GORENJEC Nina; KLEMENC KETIŠ Zalika; BLAGUS Rok; POPLAS SUSIČ Antonija (Sciendo, 2023)
Not much is known about the fall risk among the adult population of those who rarely visit doctors. We wanted to determine the prevalence of increased fall risk in a population of family practice non-attenders and the factors associated with it.